Pilot phase II study of metronomic chemotherapy in combination with bevacizumab in patients with advanced non-squamous non-small cell lung cancer. (April 2017) - Jones, Benjamin S.; Jerome, Mary S.; Miley, Deborah; Jackson, Bradford E.; DeShazo, Mollie R.; Reddy, Vishnu V.B.; Singh, Karan P.; Brown, Olivia C.; Robert, Francisco
Highlights: Metronomic chemotherapy appears tolerable and effective treatment strategy. Improved PFS and OS. Plasma biomarkers could potentially prognosticate responders to MC treatment. Abstract: Introduction: The goal of this study was to explore the efficacy and tolerability of metronomic chemotherapy, a novel anti-angiogenic treatment strategy, in combination with bevacizumab in patients with advanced non-small cell lung cancer (NSCLC). Methods: Subjects with newly diagnosed stage IV NSCLC were treated with 4-week cycles of paclitaxel 80 mg/m 2 and gemcitabine 300 mg/m 2 weekly for three weeks, plus bevacizumab 10 mg/kg every two weeks. Radiologic assessments were performed every 8 weeks. The primary endpoint was progression free survival (PFS). An exploratory objective was to correlate plasma levels of angiogenic biomarkers with treatment response. Results: Thirty-nine subjects were included in the intent to treat (ITT) analysis. The objective response rate (ORR) was 56%, the median PFS was 8.5 months, and median overall survival (OS) was 25.5 months. The PFS rate at 6, 12, and 24 months was 61%, 21%, and 11% respectively. The OS rate at 12 and 24 months was 74% and 53% respectively. Treatment was well tolerated, without significant myelosuppressive, gastrointestinal, or neurologic events. Subjects with less than median baseline values of angiopoietin-2 and IL-8 experienced significantly longer PFS. Longer OS was associated with subjects with less than the median baseline values for PLGF and angiopoietin-2. There were statistically significant differences in median values of several biomarkers between cycles 1 and 3 in subjects with objective responses. Conclusions: The combination of paclitaxel and gemcitabine, delivered in a metronomic schedule, in combination with bevacizumab, appears to be an effective and tolerable treatment strategy in patients with advanced NSCLC.